Investigating the role of the faculty advisor in doctoral students' career trajectories. Issue 5 (20th October 2019) - German, Komi T.; Sweeny, Kate; Robbins, Megan L.
ABSTRACT: During graduate school, students learn to navigate the workplace that many will seek to enter. For those pursuing an academic career, the faculty advisor is invaluable. Although research has revealed associations between advisor satisfaction and specific academic outcomes, the advisor's role in students' career prospects is unknown. Thus, the aim of this research was to investigate the advisor's role in PhD students' career trajectories, specifically their goals and outcomes on the job market. Online surveys were used in two studies: Study 1 explored the advisor's role in the career trajectories of students recently on the job market, and Study 2 surveyed PhD students just entering the job market. Study 1 revealed that those who saw their advisor as a mentor and had greater mentoring satisfaction were more likely to accept tenure-track positions and were more satisfied with their job offer. Study 2 revealed that students who talked to their advisor, regardless of mentoring satisfaction, were more likely to apply to and prioritize tenure-track positions. Taken together, our findings suggest that by serving as mentors and talking to students about the job market, advisors may facilitate the successful pursuit of tenure-track positions; however, mentoring satisfaction may depend on career outcomes.